Electronic business maturity in Portuguese SME and large enterprises - Morais, Elisabete Paulo (2011)
Since the introduction of computer technology into organizations in the 1960s, there have been numerous attempts to develop models of Information Systems/Information Technology (IS/IT)maturity. The maturity models are based on the premise that the planning process,development or adoption, use and management of IS/IT organizations, evolves through a learning process that can move through stages of maturity. If these stages (and their associated features) can be identified, could then be used to develop a plan for the IS and provide guidelines for action for the orderly progression through several stages from the current culture of the organization. This work focuses the e-business maturity stages of Portuguese SMEs (Small and Medium Enterprises) and large enterprises. Our goal is to identify in which ebusiness maturity stage they are and explore the relationship between their e-business maturity and the associated constrains to e-business evolution (previously identified in an exploratory study).